2013
DOI: 10.1007/s00404-013-2971-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle modifications in the development of diabetes mellitus and metabolic syndrome in Chinese women who had gestational diabetes mellitus: a randomized interventional trial

Abstract: Our results demonstrate a trend towards lower incidence of type II DM within 3 years postpartum in GDM women given lifestyle advice, which also potentially offers protection against development of MS, in terms of lower blood pressure and triglyceride level. Women over 40 years old are more likely to benefit. Future studies should address ways to maximize compliance to lifestyle intervention as its potential benefits can be undermined by challenges of motherhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 35 publications
0
79
1
Order By: Relevance
“…Also, the percentage of pregnant women who are performing exercise is 34.0%. Life style change is very important for women with GDM, as studies showed that changing life style decreases the probability of type 2 DM among GDM women [20]. Shek, et al 2014 in their randomized intervention study showed that lifestyle intervention can reduce the development of type 2 DM and metabolic syndrome among Chinese women who had GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the percentage of pregnant women who are performing exercise is 34.0%. Life style change is very important for women with GDM, as studies showed that changing life style decreases the probability of type 2 DM among GDM women [20]. Shek, et al 2014 in their randomized intervention study showed that lifestyle intervention can reduce the development of type 2 DM and metabolic syndrome among Chinese women who had GDM.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small number received a copy of the discharge letter sent to their GP, which summarized these verbal communications, and none have received additional written information on the risk of development of type 2 DM and adoption of a healthy lifestyle. Studies have demonstrated that lifestyle modifications including weight loss, healthy diet, and moderate exercise can reduce the risk of developing type 2 DM in high risk subjects [16, 17] and also in women with a history of GDM [1820]. For this reason, during the six-weeks postpartum visit all women with a history of GDM received information about the benefits of weight management and moderate physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…One interventional trial in Asia, which involved Chinese women with previous GDM who had impaired glucose tolerance on postpartum OGTT, offered advice on diet and exercise [103]. Fewer women who were provided the lifestyle intervention developed postpartum diabetes during a 3-year follow-up period compared with the control group, but this was without statistical significance (15% vs. 19%, p value not given).…”
Section: Interventional Modalities In Women With Gdmmentioning
confidence: 99%